Spatio-Temporal Analysis of Changes in Ecosystems of Municipal Waste Localisation Areas Using GIS and Remote Sensing Data - Azimov, O. T.; Tomchenko, O. V.; Shevchuk, O. V. (Ukrainian Geographical Journal, 2024)
The Zdovbytsia municipal solid waste (MSW) dump (the Rivne region, Ukraine) as a case study allows demonstrating informativeness of identifying waste dump sites and the adjusted areas using the spectral characteristics and texture of earth’s covers obtained from the satellite images for the different years. To identify the MSW dump in the surveyed area, direct coding features were considered, which characterized the properties of the object and are directly represented in the images. These are such features as geometric (shape, shadow, size), brightness (phototone, brightness level, color, spectral image), structural (texture, structure) ones. In addition, satellite images reliably identified discharges from the dump area, their directions, areas of unloading, damage to herbaceous cover and other vegetation, etc. The informativeness of studying the dynamics of dump geometrical parameters, the change of its internal “structure,” and the functional changes in surrounding ecosystem elements (first, in forest stands and agricultural lands) is demonstrated. In particular, satellite image data for the period of 2003 to 2021 allow identifying the increase in the number of the Zdovbytsia MSW dump sites at the expense of adjacent forest stands. Thus, in 2003, one site of the dump was operated, whereas in 2019, already three sites were integrated in 2021. The study of the dynamics of the change in the total area of the dump has revealed an increase of approximately 6.25 times (from 6,521 m2 in 2003 to 20,438 m2 in 2021). In addition, the total perimeter along the contours of its stages has increased by more than 3.35 times (from 438 to 1,466 m). The use of satellite images with a spatial resolution of about 0.6 m/pixel will specify cases of unsatisfactory conditions at the dump.